The effect of patient education on fluid compliance among haemodialysis patients / Tang Li Yoong - Tang, Li Yoong (2013)
End stage renal disease patients undergoing haemodialysis treatment is often found to be non- compliant with their treatment regime including dialysis therapy, and recommended fluid intake. Poor fluid compliance leads to hypertension and cardiovascular complications, contributing to increased mortality among the haemodialysis population. Patient education is an advocated strategy to improve compliance. This study aims to 1) assess patient knowledge on fluid and salt control, 2) determine fluid compliance status and 3) evaluate the effectiveness of patient education on fluid compliance. This is a longitudinal study, conducted using a quasi- experimental, non-equivalent group design, which took place in five hospital-based dialysis centers and involved 291 chronic haemodialysis patients who met the stipulated eligibility criteria. The patients were divided into experimental (n=154) and control group (n=137).The study consisted of two phases, aquestionnaire survey and patient records review followed by educational intervention for theexperimental group. The educational intervention included one session of individual teaching and weekly follow up for three months. The outcome measures were interdialytic weight gain (IDWG), rate of fluid adherence (RFA) and mean predialysis blood pressure (MPBP), and were assessed at one, three- and six months post-intervention.Both experimentaland control groups had no significant difference in mean total knowledge scores in the pre-intervention phase. However, there was a significant difference in mean total knowledge scores in the post-interventionphase. The experimental group had higher oddsof knowledge improvement (OR3.94,95%CI 2.02-7.69) than the control group post- intervention phase. The multivariate logistic model indicated that the number of antihypertensive medication was the only significant predictor of knowledge improvement, with higher odds (OR2.27, 95% CI 1.08-4.77) in patients who were not on any antihypertensive medication. Higher compliance improvement was found among the experimental groupatone, three- and six months post-intervention.The +experimental group had increased proportion of compliant patients in IDWG (62.8% vs. 33.3%) and RFA (50.3% vs. 20.5%)as compared to control group.There was improved compliance with regards to IDWGat 1-, 3- and6-month (1.98 kg, 1.99kg and 2.00kg respectively, p<.001) post- intervention for the experimental group.In the experimental group,RFA was improved (p<.001) compared to baseline (47.14%) at the 1- (68.54%), 3-(64.56%) and 6-(64.66%) month time –points.However, there were no significant differences(p< 0.91)in improvement in MPBP between the experimental and control group at 1-(105.47mmHg vs. 105.41mmHg), 3-(105.34mmhg vs. 106.38mmHg) and 6- (104.70 vs. 105.15 mmHg)month post- intervention. There was no predictor identified in IDWG compliance improvement. Education intervention resulted in improved knowledge and fluid compliance among haemodialysis patients. Nurses play an important role in providing ongoing education and encouragement to patients on fluid restriction and weight control. Structured and monthly scheduled education program for long-term non-compliant patients are effective in promoting and sustaining fluid compliance.